Maternal and fetal IL1RN polymorphisms and the risk of preterm delivery: a meta-analysis. (January 2015) - Cui, Junhao; Wang, Fan; Zhang, Xiaojia; Liu, Li
Abstract Objective: The aim of this study is to assess the relationship between IL1RN*2 variants and preterm delivery (PTD) risk. Methods: Eligible studies were searched in Embase and PubMed databases from inception to November 2013. Two investigators identified relevant studies and extracted data of maternal and fetal genotype independently. Based on the evidence of functional studies, we used the dominant model to all compared studies. Results: To maternal genotype, 269 PTDs and 688 controls were included in meta-analysis. The overall combined odds ratio for the IL1RN*2 variant and PTD was 1.91 (95% CI, 1.41–2.58). To fetal genotype, five studies of 322 PTDs and 858 term controls were included. The result for fetal genotype analysis showed increased risk of PTD, but not significantly (OR 1.33, 95% CI 0.99–1.78). Subgroup analysis indicated that both maternal and fetal carriage of IL1RN*2 increased the risk of PTD only in studies including preterm premature rupture of membranes (PPROM), with a pooled OR 2.02 (95% CI 1.44–2.85) and 1.42 (1.02–1.99), respectively. Conclusions: This meta-analysis suggests that maternal carriage of IL1RN*2 were associated with increased risk in PTD. PPROM may be an important confounding factor that should be taken into consideration for study of IL1RN polymorphism and PTD.